P1 The potential for pharmacists to manage young patients attending emergency departments. Issue 2 (19th January 2018) - Terry, David; Huynh, Chi; Petridis, Konstantinos; Aiello, Matthew; Sinclair, Anthony; Mazard, Louis; Terry, Alex; Ubhi, Hirminder; Wilson, Keith; Hughes, Elizabeth
Abstract : Background: There have been concerns about maintaining appropriate clinical staff levels in Emergency Departments in England. 1 One possible solution to alleviating the workforce pressure is the extension of clinical activity performed by non-medical staff – including pharmacists. 2 Aims and objectives: To determine if Emergency Department attendees aged from 10–25 years (adolescents) could be clinically managed by community pharmacists or hospital pharmacist independent prescribers with or without further advanced clinical practice training. Method: A prospective 49 site cross-sectional observational study of patients attending Emergency Departments (ED) in England, UK. Each site was requested to collect data for 400 admissions of all ages. Pharmacist independent prescribers (one for each site) were asked to identify patient attendance at their Emergency Department, record anonymised details of the cases – age, weight, presenting complain, clinical grouping (e.g. medicine, orthopaedics) and categorise each one into one of four possible categories: CP, Community Pharmacist, cases which could be managed by a community pharmacist outside an ED setting; IP – cases that could be managed in ED by a hospital pharmacist with independent prescriber status; IPT, Independent Prescriber Pharmacist with additional training – cases which could be managed in ED by a hospital pharmacist independent prescriber with additional clinical training; and MT, Medical Team only – cases that were unsuitable for the pharmacist to manage. An Impact Index was calculated for the two most frequent clinical groupings using the formula: Impact index (I)=proportion of the total workload of the clinical grouping (w) multiplied by the percentage ability of pharmacists to manage that clinical group (a). I=wa. The higher the Impact Index the greater potential for pharmacists to support the clinical workload related to that group. Results: 2993 out of 18 613 (16%) attendees were young patients aged from 10 to 25 years of age (median 20 years, interquartile range 17–22 years) of which 1530 were female and 1463 were male. Of the 2993 patients, 6% of the cases were judge to be suitable for the community pharmacist (CP), 5% suitable for a hospital pharmacist independent prescriber (IP), 37% were deemed as suitable for a hospital independent prescriber with additional training (IPT) and the remaining 52% were only suitable for the medical team (MT). The most frequent clinical groups and Impact Index were general medicine=16.97 and orthopaedics=15.51. Conclusion: Emergency Department attendees who were young patients were judged by independent prescriber pharmacists to be suitable for clinical management by community pharmacists outside a hospital setting in approximately 1 in 16 admissions, and by a hospital independent prescriber pharmacists in 1 in 20 cases. With further training, it was found that the total proportion of cases that could potentially be managed by a pharmacist (CP, IP or IPT) came to 48%. The greatest potential impact for pharmacist management occurs in general medicine and orthopaedics. References: Paw RC. Emergency Department Staffing in England and Wales. Emer Med J 2008;24:420–23. Hughes E, et al . Future enhanced clinical role of pharmacists in Emergency Departments in England: Multi-site observational evaluation. Int J Clin Pharm 2017;39:960–968.